2018
DOI: 10.1016/j.apsusc.2018.02.263
|View full text |Cite
|
Sign up to set email alerts
|

The effects of phase transformation on the structure and mechanical properties of TiSiCN nanocomposite coatings deposited by PECVD method

Abstract: In the present study, the effects of phase transformations on the structure and mechanical properties of TiSiCN coatings were investigated. TiSiCN nanocomposite coatings were deposited on AISI H13 hot-work tool steel by a pulsed direct current plasma-enhanced chemical vapor deposition process at 350 or 500 °C, using TiCl4 and SiCl4 as the precursors of Ti and Si, respectively, in a CH4/N2/H2/Ar plasma as the source of carbon and nitrogen and reducing environment. Some samples deposited at 350 °C were subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Among this class of coating materials, nanocomposite coatings of the TiSiN [3][4][5][6] and TiSiCN [3,4,[7][8][9][10] families have received a greater attention during the last two decades.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among this class of coating materials, nanocomposite coatings of the TiSiN [3][4][5][6] and TiSiCN [3,4,[7][8][9][10] families have received a greater attention during the last two decades.…”
Section: Introductionmentioning
confidence: 99%
“…Industrial research is focusing on TiSiCN coatings for their versatility in both processing and use, addressing diverse demanding applications, as recent work suggests, such as high speed machining in dry or near-dry conditions [4] coating of piston rings [11], and of prosthesis components [12]. The availability of different processes for the deposition of TiSiCN coatings -namely Chemical Vapor Deposition, CVD [6][7], Plasma Enhanced (PE) CVD [5][6][7][8], sputtering [13] and plasma enhanced sputtering arc ion plating [14] has been influential to its industrial implementation by enabling processing in a wide range of conditions and tailoring of material properties. The microstructure of this coating -formed through selforganization as a result of spinodal transformation-consists of an amorphous matrix of silicon nitride or silicon carbonitride with a dispersion of TiCN nanocrystals [4,7,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For TiAlN-PVDMNC cutting tools, flank wear is much higher due to the inability to withstand higher temperatures at higher cutting speeds. In the case of TiAlSiN-PECVD cutting tools, high lubrication of SiN reduces the heat generation [21]. It is seen from SEM image as shown in figure 12 that the wear path of TiAlN cutting tools is much thicker leading to high wear on the flank nose area when it is operated at higher speeds and feed rates.…”
Section: Flank Wear Measurementmentioning
confidence: 99%
“…Ma et al [20] exposed the effect of TiAlSiN nanocomposite coated cutting tools on the voltage bias environment. Abedi et al [21] investigated the PECVD and PVD-CVD coatings of TiSiCN and concluded that PECVD coating is better than PVD-CVD coatings.…”
Section: Introductionmentioning
confidence: 99%